Pengaruh Innovation dan Service Quality terhadap Customer Satisfaction melalui Customer Trust - Devi Eka Sari (JURNAL EKOBIS DEWANTARA, 2018)
This research is conducted to know the influence of innovation and service quality to customer satisfaction through customer trust at Pamella Supermarket Yogyakarta. Research location in Yogyakarta. The population of this study are customers living in Yogyakarta. The sample of 100 respondents taken using accidental sampling technique of data collection method using questioner. Data analysis used is descriptive analysis, multiple regression analysis and path analysis. The results of this study indicate that innovation has significant effect on customer trust; service quality has significant effect on online repurchase intention; and customer trust have a significant effect on customer satisfaction